Paesaggi, fiumi ed acque: l’impegno dell’Autorità di bacino del fiume Tevere - Roberto Grappelli; Remo Pelillo (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The evolution of the landscape and its representation scale are appropriate to the prospect and the scale of basin planning. The river Tevere basin Authority acts on the tecnique tradition that made its decision related to landscape features. Flood prevention and soil protection policy. The big flood plains on the north of Rome are in defence of the city. The protection of the big flood plains is the target of the Authority planning, that is to say to protect the landscape. Water resources policy. The river Tevere has two hydrological states, one is as the Paglia river and the other is as the Nera river. The tradition has used these hydrological states and it has built three water schemes on them. The Authority will organize these water schemes in a single water system.